The Urgency of Philosophy of Science for Doctoral Students of Law - Purnomo, Vicki Dwi; Heri Santoso; Edy Lisdiyono (PT FORMOSA CENDEKIA GLOBAL, 2024)
Philosophy of science plays a very important role for doctoral students in law, because it provides a critical, reflective, and in-depth foundation for thinking in conducting advanced legal research. This article discusses the urgency of philosophy of science for doctoral students in law from several main aspects, including epistemological and ontological foundations, development of theoretical frameworks, critical evaluation of scientific methods, and improvement of legal reasoning skills. Philosophy of science also provides ethical guidance in research and helps students understand the relationship between law and other disciplines, such as sociology and politics. Through a deeper understanding of philosophy of science, doctoral students in law can compile more comprehensive, relevant, and impactful research, and make significant contributions to the development of legal science in the future.